The improvement of Coreopsis tinctoria essential oil on learning and memory impairment of d-galactose-induced mice through Nrf2/NF-κB pathway - Qu, Yan; Guo, Yingxue; Li, Wenpeng; Shen, Hongkuan; Cui, Jiwen; Li, Jinlian; Liu, Jiguang; Wu, Dongmei (Frontiers in Pharmacology, 2022)
Essential oil of Coreopsis tinctoria (EOC) is a essential substance extracted from Coreopsis tinctoria with the excellent anti-oxidant effect. However, it is still unclear whether EOC can improve learning and memory impairment and its mechanism. The purpose of this study was to investigate the effect of EOC on learning and memory impairment induced by D-galactose(D-gal) in mice and reveal its mechanism. The composition of EOC was analyzed by GC-MS, and the results showed that the highest content was D-limonene. The follow-up experiments were conducted by comparing EOC with D-limonene. The aging model was established by subcutaneous injection of D-gal, and donepezil, D-limonene and EOC were given by intragastric administration. It was found that EOC and D-limonene significantly improved learning and memory impairment induced by D-gal through the Morris water maze and step-through tests. Pathological and biochemical analysis showed that the hippocampal morphologic of mice was damage and the activities of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) induced by D-gal were decreased, while the content of malondialdehyde (MDA) was increased, while EOC and D-limonene could reverse the morphological changes and reduce oxidative damage. In addition, EOC and D-limonene significantly increased body weight and organ coefficients, including liver, spleen and kidney. Moreover, EOC and D-limonene improved the expression of nuclear factor E2 related factor 2 (Nrf2) pathway and inhibited nuclear transcription factors-κB (NF-κB) pathway. In summary, the results showed that EOC and D-limonene could improve learning and memory impairment induced by D-gal through Nrf2/ NF-κB pathway. It was clear that as a mixture, EOC was better than D-limonene on improving learning and memory impairment.